An open label randomized phase II study of pasireotide with or without everolimus in castrate-resistant chemotherapy-naïve prostate cancer patients. (2015) - Lin, Jianqing; Deng, Aileen; Hoffman-Censits, Jean; Gibney, Geoffrey; Hyslop, Terry; Miller, Brooke; Kilpatrick, Deborah; Jabbour, Serge; Kevin Kelly, William
Abstract: New areas of research continue to examine the role of non-androgen receptor pathways in prostate cancer treatment. The phosphatidylinositol 3-kinase/Akt/mammalian target of rapamycin (mTOR) pathway may be a target for prostate cancer therapy. Somatostatin receptor signaling inhibits intracellular PI3K/Akt signaling, making it an attractive target for combination therapy. We conducted a phase II open label clinical trial examining the use of somatostatin receptor agonist, pasireotide (SOM230) in combination with mTOR inhibitor, everolimus in metastatic castrate-resistant chemotherapy-naïve prostate cancer patients. Of the 6 patients enrolled in the study, only 1 patient had >50% PSA reduction from baseline. Three patients withdrew due to grade 3 adverse events. The study was closed early due to toxicity profiles and no further development was planned for this combination treatment in prostate cancer.